(untitled) (Fiep Bulletin - online, 2012)
Introduction: In Brazil, as in many parts of world, soccer is a national passion. In 1863, representatives from university and clubs from England met at London, with the aim to unify the rules of the soccer game. This soccer evolution, made with the coaches cared more with the tactical aspects of the game. Objective: The aim of the present study is to analyze the incidence of goals in the first turn of the first division of 2011 Brazilian Championship. Methods: Were analyzed 189 matches, for the first round games of the 2011 Brazilian championship, total of 500 goals. Was realized the chi-square test to determine significant differences on the match time and the level of significance was set in p<0,05. Results: The present study showed that the goals during the first round games of the 2011 Brazilian championship are not equally distributed between time intervals (chi-square values 12,736 and p<0,05). Thus a higher incidence of goals was observed between 76 to 90 minutes (22,2%). Discussion: The results of the present study, showed that on the first round games of 2011 Brazilian championship, the goals are in larger amount in the second half (55.2%), compared to the first. When this analysis is done in parts, there is a higher incidence of goals in the final 15 minutes of the second half of matches (22.2%). The reasons for these results still have been target of studies, since it is not clear in the literature which the most important factor for this increase in the number of goals in the final moments of games.